Nordic Seas polynyas and their role in preconditioning marine productivity during the Last Glacial Maximum - Knies, Jochen; Koseoglu, Denizcan; Rise, Leif; Baeten, Nicole; Bellec, Valerie K; Bøe, Reidulv; Klug, Martin; Panieri, Giuliana; Jernas, Patrycja Ewa; Belt, Simon T. (Nature Communications, 2018)
Source at https://doi.org/10.1038/s41467-018-06252-8 . Arctic and Antarctic polynyas are crucial sites for deep-water formation, which helps sustain global ocean circulation. During glacial times, the occurrence of polynyas proximal to expansive ice sheets in both hemispheres has been proposed to explain limited ocean ventilation and a habitat requirement for marine and higher-trophic terrestrial fauna. Nonetheless, their existence remains equivocal, not least due to the hitherto paucity of sufficiently characteristic proxy data. Here we demonstrate polynya formation in front of the NW Eurasian ice sheets during the Last Glacial Maximum (LGM), which resulted from katabatic winds blowing seaward of the ice shelves and upwelling of warm, sub-surface Atlantic water. These polynyas sustained ice-sheet build-up, ocean ventilation, and marine productivity in an otherwise glacial Arctic desert. Following the catastrophic meltwater discharge from the collapsing ice sheets at ~17.5 ka BP, polynya formation ceased, marine productivity declined dramatically, and sea ice expanded rapidly to cover the entire Nordic Seas.